2019
DOI: 10.1002/jcla.23007
|View full text |Cite
|
Sign up to set email alerts
|

Determination of high‐sensitivity cardiac troponin T upper reference limits under the improved selection criteria in a Chinese population

Abstract: Background:There is no common consensus on how to define the reference population for determination of high-sensitivity cardiac troponin (hs-cTn) upper reference limit (URL). This study aimed to establish 99th percentile URLs of hs-cTnT under both 2018 AACC/IFCC criteria and improved selection criteria for further judging whether two URLs are different. Methods:Applying the stratified cluster sampling protocol, this study took 1848 apparently healthy subjects in communities of Shenyang China as the screening o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Indeed, the 10% of cTnI values, measured with high-sensitivity methods in a large Italian population, are actually lower than 2 ng/L [19]. Considering the cTnT assay, about 20-25% of apparently healthy adult European and Chinese men and women [20][21][22] showed cTnT values ≤3 ng/L (i.e., the LoD of the method).…”
Section: Analytical Performances and Pathophysiological Interpretatiomentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the 10% of cTnI values, measured with high-sensitivity methods in a large Italian population, are actually lower than 2 ng/L [19]. Considering the cTnT assay, about 20-25% of apparently healthy adult European and Chinese men and women [20][21][22] showed cTnT values ≤3 ng/L (i.e., the LoD of the method).…”
Section: Analytical Performances and Pathophysiological Interpretatiomentioning
confidence: 99%
“…From a pathophysiological perspective, several authors have suggested that the circulating levels of hs-cTn measured in healthy adult subjects should be considered a reliable index of the physiological cardiomyocyte renewal [14][15][16][17][18][19][23][24][25], which is defined as the ability to replace loss of cardiomyocytes by new ones [26]. In particular, some recent clinical studies report that the 99th percentile URL values of hs-cTn methods are on average ranging from 13 to 47 ng/L [13,[17][18][19][20][21][22], corresponding to about 30-40 mg of cardiomyocyte renewal [17,23,24]. Accordingly, the mean hs-cTn concentrations of about 3-5 ng/L, typical of adult healthy subjects, are related to a myocardial volume ≤10 mg.…”
Section: Analytical Performances and Pathophysiological Interpretatiomentioning
confidence: 99%
“…Approaches to sequentially exclude patients from reference populations used to derive the 99th centile using such testing has been shown to affect the threshold level, in particular, in older patients. 8,38,39 Of note, the addition of comorbidities to our baseline model resulted in an improvement in model discrimination, suggesting that approaches which consider multiple individual patient factors could offer an alternative to threshold-based diagnosis. 40 One such example is the myocardial infarction 3 model that uses machine learning to provide individual probability estimates and has been shown to perform favorably in an observational study with superior specificity and PPV compared with universal thresholds.…”
Section: Discussionmentioning
confidence: 99%
“…Approaches to sequentially exclude patients from reference populations used to derive the 99th centile using such testing has been shown to affect the threshold level, in particular, in older patients. 8 , 38 , 39 …”
Section: Discussionmentioning
confidence: 99%
“…Subjects who reported no cardiovascular disease or medication use performed an electrocardiogram (ECG), a physical examination, and laboratory testing. Exclusion criteria included pregnancy, a recent blood transfusion or blood donation, hypertension, individuals under 20 years old, HbA1c >6.5% (alternative biomarker of diabetes), eGFR ≤60 mL/min/1.73 m 2 (alternative biomarker of renal dysfunction), N-terminal-pro-B-type natriuretic peptide (NT-proBNP) >125 pg/mL (<75 years) or 450 pg/mL (≥75 years) (alternative biomarker of myocardial dysfunction), overweight or obesity (body mass index ≥25.0 kg/m 2 ), and the history of dyslipidemia or TG >2.3 mmol/L, total cholesterol >6.2 mmol/L, low-density lipoprotein >4.1 mmol/L, and high-density lipoprotein ≤1.0 mmol/L [ 11 ]. According to the principles of Helsinki declaration, this study was approved by the Ethics Committee of the First Hospital of Jilin University.…”
Section: Methodsmentioning
confidence: 99%